Recursos didácticos en el área de artes visuales y su incidencia en la profesionalización del docente de educación básica año 2014 - Ordoñes Amores, Nancy Yolanda (2015)
The thesis addresses a problem related to the use of teaching resources in the area of Visual Arts in Basic Education, the theoretical framework that sustain the research process are studied and the preparation of the proposal, is made a study of the contextual reality of an educational institution from conducting surveys and interviews and was design and argues a didactic proposal for teaching Visual Arts learning supported by the use of images referred mainly to the work of the Ecuadorian painter Oswaldo Guayasamin which they are of particular educational significance.